1819. Antibiotic Prescribing Feedback: Description of Denominator Metrics to Standardize Prescribing Rates for Peer Comparison. (26th November 2018) - Jones, Travis; Johnson, Melissa; Moehring, Rebekah W; Ashley, Elizabeth Dodds
Abstract: Background: Prescriber feedback on antibiotic use (AU) paired with peer comparison reduces inappropriate antibiotic prescribing in the outpatient setting but is challenging to replicate in hospitals. Measuring overall AU in days of therapy (DOT) by prescriber does not adequately identify outliers because patient volumes differ greatly between providers. We employed various novel denominator metrics in order to facilitate peer comparison between prescribers in the inpatient setting and report prescriber-specific AU rates. Methods: Antibiotic DOT were obtained for physicians at two community hospitals. Data were obtained from electronic medication administration records linked to ordering provider. Physician-specific data for patient days (count of patient days of which physician was attending of record), patients seen (daily count of patients on provider rounding list), patient admissions, and shifts worked, were obtained from routine hospital datasets. Changes in rates and rank were compared for denominator metrics. Results: A total of 36, 828 DOT were included for 56 physicians at two hospitals. Prescriber rank changed for all top five prescribers at each hospital after incorporating physician-specific denominator metrics as compared with DOT alone (Table 1). The largest change in rank observed was 19 spots using admissions as a denominator. Conclusion: Incorporating physician-specific denominator metrics to account for differences in patient volume enhances peer comparison and results in significant changes in prescriber rank. Choice of meaningful denominator is highly dependent on staffing model for hospital physicians. Disclosures: All authors: No reported disclosures.